ChemInform Abstract: Direct Reductive Amination of Aldehyde Bisulfite Adducts Induced by 2‐Picoline Borane: Application to the Synthesis of a DPP‐IV Inhibitor. Issue 28 (21st June 2013) - Faul, Margaret; Larsen, Rob; Levinson, Adam; Tedrow, Jason; Vounatsos, Filisaty
Abstract The title reaction allows an efficient access to a wide range of secondary amines including the DPP‐IV inhibitor (VIII).